Integration of Indigenous healing practices of the Kali Cult with Western psychiatric modalities in British Guiana - Singer, Philip; Aarons, Louis; Araneta, Enrique (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Modern methods of psychiatric therapy have been integrated with traditional techniques in Africa, notably in Nigeria and Ghana. A review of Latin American psychiatry shows no activity in this area. One exception seems to be British Guiana. This country has sometimes been called an island surrounded by land, because of its unique ethnic composition, and persistence of cultural identity’ of origin, (51% East Indian, 31% African, 1 1 % "mixed,” 4% Amerindian, and the rest a smattering of Portuguese, Chinese and "other” Europeans).